Welfare States, Labor Markets, Social Investment and the Digital Transformation - Werner Eichhorst; Anton Hemerijck; Gemma Scalise (Institute of Labor Economics (IZA), 2020)
Barely having had the time to digest the economic and social aftershocks of the Great Recession, European welfare states are confronted with the even more disruptive coronavirus pandemic as probably, threatening the life of the more vulnerable, while incurring job losses for many as the consequence of the temporal "freezing of the economy" by lockdown measures. Before the Covid-19 virus struck, the new face of the digital transformation and the rise of the 'platform' economy already raised existential questions for future welfare provision. The Great Lockdown - if anything - is bound to accelerate these trends. Greater automation will reinforce working from home to reduce Covid-19 virus transmission risks. At the same time, the Great Lockdown will reinforce inequality, as the poor find it more difficult to work from home, while low-paid workers in essential service in health care, supermarket retail, postal services, security and waste disposal, continue to face contagion risks. And although popular conjectures of 'jobless growth' and 'routine-biased' job polarization, driven by digitization and artificial intelligence, may still be overblown, intrusive change in the nature of work and employment relations require fundamental rethinking of extant labour market regulation and social protection. Inspired more by adverse family demography than technological change, social investment reform has been the fil rouge of welfare recalibration since the turn of the century. Is social investment reform still valid in the new era of 'disruptive' technological transformation in aftermath of Coronavirus pandemic that is likely to turn into the worst recession since the second world war? Empirically, this chapter explores how Germany, Italy and the Netherlands, in terms of the strengths and vulnerabilities of their labour market to digitization, together with their respective social investment aptitude, are currently preparing their welfare states for the intensification of technological change in the decade ahead.
Keywords: J21; J24; J42; 330; COVID-19; Italy; technological change; Netherlands; social investment; digital transition; Germany